The role of personal and sports values on intentions to compete clean or to cheat - Beatričė Hoppen (Baltic Journal of Sport and Health Sciences)
Background and objectives: Cheating is defined as the voluntary violation of established rules, characterized by an element of deception (Green, 2006). The opposite of cheating is clean sport (Petróczi et al., 2021). A recent study revealed that up to 57.1 % athletes are using doping (Ulrich et al., 2018). Cheating in sports is associated with various factors (internal and external), but a particularly important yet less studied internal factor is values. Based on Schwartz’s (1992) theory of personal values, four higher-level value dimensions are identified: self-enhancement, self-transcendence, openness to change, and conservation. However, athletes’ intentions and behavior can be influenced not only by personal values, but also by sports values. Lee et al. (2000) identified such sports values as morality, competence and status. Depending on which values are more important to athletes, they may be inclined to behave one way or another, for example, to cheat in sports or to compete clean. Purpose of the research is to reveal the role of values in athletes’ intentions to compete clean or to cheat in sport.